2009
DOI: 10.1148/radiol.2531082049
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Zone Prostate Cancer in Patients with Elevated PSA Levels and Low Free-to-Total PSA Ratio: Detection with MR Imaging and MR Spectroscopy

Abstract: MR and MR spectroscopy combined with free-to-total PSA ratio improves the predictive value for prostate cancer detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In the literature, there currently is no consensus about the use of 1 H-MRS for prostate cancer detection (3)(4)(5). We quantitatively analyzed all voxels containing prostatic tissue, eliminating the investigator-dependent variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there currently is no consensus about the use of 1 H-MRS for prostate cancer detection (3)(4)(5). We quantitatively analyzed all voxels containing prostatic tissue, eliminating the investigator-dependent variations.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with TRUS, MRI has demonstrated a much higher sensitivity for tumor detection but almost the same specificity (2), stressing the need for additional metabolic MRI. Proton MR spectroscopy ( 1 H-MRS) has the ability to depict possible cancer in all parts of the gland volume and assist in staging (3)(4)(5). However, 1 H-MRS currently still has several disadvantages such as long acquisition times and the common use of an endorectal coil (6).…”
mentioning
confidence: 99%
“…Increased levels of choline-containing metabolites have been observed in vivo by 1 H-MRS in many cancers including those of the brain, prostate and breast (Leach et al, 1998;Howe et al, 2003;Vilanova et al, 2009). The same technique has also shown that patient treatment with chemotherapy or radiation was associated with a decline in these signals (Leach et al, 1998;Meisamy et al, 2004).…”
Section: Pantaleomentioning
confidence: 96%
“…Because only a handful of these agents have so far gained FDA approval, and the fact that most are still in pre-clinical development or early-phase clinical testing, most of the MRS studies performed to date have been concerned with pre-clinical cancer models, including cells and tumour xenografts. However, the technology has been demonstrated in a range of diagnostic and response assessment clinical studies (Howe et al, 2003;Meisamy et al, 2004;Vilanova et al, 2009).…”
mentioning
confidence: 99%
“…Furthermore, the reference ROIs in nonmalignant tissues may have contained small tumour contributions that were not visible on the images. The same approach, however, has already been taken by other groups [24][25][26] and is deemed feasible here, because the primary goal was not the correlation of MRI lesions of the entire prostate to histopathology but to investigate the influence of the choice of b values. Even with whole-mount sections, the matching of MRI lesions to histopathological findings is not free of bias and errors [5,24].…”
Section: A Significant Influence Of the Choice Of B Values On The Absmentioning
confidence: 99%